How does surfactant aid the displacement of oil by water in nanoscale cracks?. (15th August 2023) - Zhang, Zechen; Ducker, William A.
Graphical abstract: Highlights: Displacement of oil by water depends on surfactants forming reverse micelles. An increase in the water content of the oil enhances displacement of oil by water. The water phase does not need to be continuous to displace oil from a hydrophilic solid. A decrease in oil–water interfacial tension is not sufficient to allow displacement. Abstract: The displacement of oil by water is the central concern in enhanced oil recovery. In this paper, we present an experimental study of the displacement of oil by water in a nano-scale, glass channel. The channel was 100 nm thick, composed of hydrophilic glass, and was closed at one end. Displacement was examined under zero applied pressure. Three surfactants were examined for their ability to aid displacement of oil: sodium dodecylsulfate (SDS), an anionic surfactant; Aerosol OT (AOT), an anionic surfactant; and dodecyltrimethylammonium bromide (DTAB), a cationic surfactant. AOT was the only surfactant that caused displacement of oil within 12 h. AOT is also the only one of the three surfactants that can form reverse micelles in the oil phase, and we attribute the oil displacement to the delivery of water to the hydrophilic glass by reverse micelles. We support this conclusion with experiments showing (a) lesser displacement with fewer reverse micelles and (b) that the water phase is discontinuous. The latter implies transport of water through the oil phase. Therefore, the conclusion of this work is that the surfactant aids oil recovery from a hydrophilic channel by enhancing transport of water through oil. The delivered water can adsorb at the solid and continued transport can spontaneously grow a bulk water phase, thereby displacing the oil.